Spontaneous Osteogenesis of a Traumatic Mandibular Defect in the Pediatric Population. Issue 7 (October 2019) - Gornitsky, Jordan; Azzi, Alain Joe; Cugno, Sabrina
Abstract : Abstract: Spontaneous osteogenesis of traumatic mandibular defects in the pediatric population remains a relatively rare phenomenon with only 2 patients reported in the literature. In the adult population, a low threshold exists for bone graft placement in the presence of small mandibular gaps, with no role for spontaneous osteogenesis in significant mandibular defects. The approach to traumatic mandibular defects in the pediatric population is not clearly described in the literature and the risks and benefits associated with donor site morbidity of bone graft harvest must be tempered by the possibility for potential spontaneous osteogenesis. The present study reports 1 such patient in whom a significant mandibular defect healed by means of rigid fixation of the defect and spontaneous osteogenesis, with no functional or esthetic sequelae at long-term follow-up. A review of the pertinent literature was performed, and the authors' approach is discussed. The authors propose that traumatic mandibular defects of < 3 cm in patients under the age of 10 years should be considered for treatment with rigid internal fixation alone and spontaneous osteogenesis.